2016
DOI: 10.1155/2016/6705431
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Polyphenolic Compounds in Extracts from Leaves of SomeMalus domesticaCultivars: Antiradical and Antimicrobial Analysis of These Extracts

Abstract: In this study, methanol, ethyl acetate, water extracts, and precipitate were obtained from leaves of Malus domestica cultivars: Golden delicious, Jonagold, Elstar, Ligol, and Mutsu. Antiradical activity of these extracts was measured using the ABTS+∙ radical, and antimicrobial activity was measured with the disk-diffusion method. Phenolic compounds were measured with the colorimetric method and identified with high performance liquid chromatography (HPLC). The highest antiradical activity was observed for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…In some experimental models, phloridzin exhibited antibacterial and antifungal activity. Sowa et al [ 88 ] observed that extracts of Malus domestica leaves (containing a large amount of phloridzin) had antibacterial and antifungal activity by the inhibition of Staphylococcus aureus and Enterococcus faecalis and the fungus Candida glabrata . Lopes et al [ 89 ] found that phloridzin was effective in inhibiting biofilm formation in Staphylococcus aureus strains, which increased efflux protein genes.…”
Section: Therapeutic Properties Of Phloridzinmentioning
confidence: 99%
“…In some experimental models, phloridzin exhibited antibacterial and antifungal activity. Sowa et al [ 88 ] observed that extracts of Malus domestica leaves (containing a large amount of phloridzin) had antibacterial and antifungal activity by the inhibition of Staphylococcus aureus and Enterococcus faecalis and the fungus Candida glabrata . Lopes et al [ 89 ] found that phloridzin was effective in inhibiting biofilm formation in Staphylococcus aureus strains, which increased efflux protein genes.…”
Section: Therapeutic Properties Of Phloridzinmentioning
confidence: 99%
“…The phenolic composition of apple fruits has been thoroughly investigated [35][36][37]40,[45][46][47][48]. However, there exist only a few studies on the contents of these compounds in the individual organs of apple trees [49][50][51]. These studies indicate significantly higher levels of phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The other isolated biomolecule obtained from A. columbrina was p -hydroxybenzoic acid, which showed activity against S. aureus UFPEDA02; however, it did not show inhibitory action towards the DPPH radical. The weak antiradical activity of p -hydroxybenzoic acid was observed by other authors [67]. In contrast, this compound has been pointed as antimicrobial agent against S. aureus , Staphylococcus epidermis , Escherichia coli , Pseudomonas aeruginosa , and Salmonella typhimurium [33,68,69], an effect usually associated with its relative hydrophobicity [70].…”
Section: Discussionmentioning
confidence: 99%